PENGARUH TEAM WORK, KOMITMEN ORGANISASI DAN PENGEMBANGAN TERHADAP KINERJA PEGAWAI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KOTA SIBOLGA - Ade Irma Suryani; Riwayani Riwayani; Tengku Aziddin; Bayu Safri Ananda; Ratna Dewi (Manajemen dan Bisnis, 2022)
This formula research internal issue is how influence team work on employeesperformance.  Howinfluence  oforganization  coomitment  xx  on  employeesperformance.Howinfluence  ofdevelopmenton  employeesperformance.  How  influenceofteam  work,organizationcoomitment,and developmenton employees  performance. This research target is to for know        influence and analyze of   team work on employees  performance. For know influence and analyzeof  organization  coomitmenton  employees   performance.  For  knowinfluenceand  analyzedevelopment   on  employeesperformance.  For  know  influence  andanalyzeteam  work,organization coomitment and development on employees  performanceSample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of team work effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance. Team work, organization coomitment, and development effect and positive and significant on employees performanceThis formula research internal issue is how influence team work on employeesperformance.  Howinfluence  oforganization  coomitment  xx  on  employeesperformance.Howinfluence  ofdevelopmenton  employeesperformance.  How  influenceofteam  work,organizationcoomitment,and developmenton employees  performance. This research target is to for know        influence and analyze of   team work on employees  performance. For know influence and analyzeof  organization  coomitmenton  employees   performance.  For  knowinfluenceand  analyzedevelopment   on  employeesperformance.  For  know  influence  andanalyzeteam  work,organization coomitment and development on employees  performanceSample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of team work effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance. Team work, organization coomitment, and development effect and positive and significant on employees performance